Not Welcome Anymore: The Effect of Electoral Incentives on the Reception of Refugees - Matteo Gamalerio (Center for Economic Studies and ifo Institute (CESifo), 2018)
Do electoral incentives affect immigration policies? I study this question in the setting of Italian municipalities making decisions about the reception of refugees. The localized control of the reception policy (SPRAR), combined with the exogenous timing of policy decisions and staggered elections, enables me to study the effect of electoral incentives on the reception of refugees. Although municipalities receive fiscal grants for hosting refugees, electoral incentives reduce the probability of opening a refugee centre by 24 per cent. The effect is driven by voters' misperceptions of immigrants and by extreme-right political preferences. The results explain why is difficult to reach an equal redistribution of refugees across and within countries.
Keywords: R23; J61; D72; C23; 330; migration; reception of refugees; electoral incentives; fiscal grants